2017
DOI: 10.1016/j.eurpsy.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Stress, attention deficit hyperactivity disorder (ADHD) symptoms and tobacco smoking: The i-Share study

Abstract: Stress and ADHD contribute independently to the risk of smoking. Interventions targeting each condition are likely to reduce the burden of tobacco use in students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…This shows that students are always under constant fear of getting low grades irrespective of their current GPAs. Similar to a previous study that looked at the association between ADHD symptoms and smoking, which concluded that the relationship was significantly positive [13], the current study found a high percentage of smokers among the medical users of stimulants compared to the non-users group (79.5% and 18.7%, respectively).…”
Section: Illicit Use (N = 29)supporting
confidence: 86%
“…This shows that students are always under constant fear of getting low grades irrespective of their current GPAs. Similar to a previous study that looked at the association between ADHD symptoms and smoking, which concluded that the relationship was significantly positive [13], the current study found a high percentage of smokers among the medical users of stimulants compared to the non-users group (79.5% and 18.7%, respectively).…”
Section: Illicit Use (N = 29)supporting
confidence: 86%
“…Barriers to healthy dietary choices were also found among Sri Lankan school children [25]. Moreover, academic and psychological stress are found to be associated with alcohol consumption [26] and cigarette smoking [27]. Considering the above facts, Sri Lankan AL students could have potential risk factors for GORD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, nicotine dependence assessed by the HSI yielded no genetic association in the present sample, suggesting that the genetic influence of nAChRs may rather exert on the number of CPD than on other symptoms of loss of control over nicotine intake. In this population, both phenomena may thus rely on more distinct risk factors than in the general population, suggesting that tobacco smoking may further be used to cope with other drugs craving/adverse effects [33] or attention deficits [34], which may overall be mediated by the relationship of these symptoms with perceived stress [35]. The discrepancy between CPD and HSI has been previously reported [36], and HSI itself remains a proxy for the full DSM nicotine dependence syndrome.…”
Section: Discussionmentioning
confidence: 73%